2012
DOI: 10.4137/grsb.s9687
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Transcriptome Responses of the Rumen Epithelium to Butyrate Infusion using RNA-seq Technology

Abstract: Short-chain fatty acids (SCFAs), such as butyrate, produced by gut microorganisms, play a critical role in energy metabolism and physiology of ruminants as well as in human health. In this study, the temporal effect of elevated butyrate concentrations on the transcriptome of the rumen epithelium was quantified via serial biopsy sampling using RNA-seq technology. The mean number of genes transcribed in the rumen epithelial transcriptome was 17,323.63 ± 277.20 (±SD; N = 24) while the core transcriptome consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 57 publications
(103 reference statements)
3
52
0
Order By: Relevance
“…In an another bovine RNA-seq experiment on rumen epithelium tissue, the study of Baldwin and co-workers found that ~71% of the reads were mapped onto ~17,000 different genes of Bos taurus reference genome [33]. …”
Section: Discussionmentioning
confidence: 99%
“…In an another bovine RNA-seq experiment on rumen epithelium tissue, the study of Baldwin and co-workers found that ~71% of the reads were mapped onto ~17,000 different genes of Bos taurus reference genome [33]. …”
Section: Discussionmentioning
confidence: 99%
“…It was recently found that TGFB1 is regulated in grain induced ruminal development in dairy calves (Connor et al, 2014). In contrast, TGFB1 was shown to be downregulated in lactating dairy cattle infused with butyrate (Baldwin et al, 2012). The discrepancy found in TGFB1 mRNA expression responses between growing versus adult cows may be due in part to differences in the functions of TGFB1 in calf versus adult RE.…”
Section: Transforming Growth Factor βmentioning
confidence: 91%
“…Connor et al (2014) observed an increase in TGFB1 expression in ruminating calves and hypothesized it was a mechanism to reduce calf ruminal cell proliferation likely mediated by butyrate from rumen fermentation. However, in adult ruminants no effect of butyrate on TGFB1 in ruminal epithelium was observed (Baldwin et al, 2012). Connor et al (2014) suggested that TGFB1 may play different roles in adult than young ruminal epithelium.…”
Section: Gene Expression In Ruminal Epithelium During Transitionmentioning
confidence: 96%